Readiness of Lecturers As A Facilitator In Interprofessional Education Learning In Antenatal Care - Fuadah, Dina Zakiyyatul; Taukhid, Muhammad (Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Background: Many educational institutions in Indonesia are familiar with the concept of interprofessional learning or interprofessional education but not many have applied. Facilitator readiness, one of the causes of this method has not been implemented optimally. Purpose: This study aims to determine the readiness of the lecturer as a facilitator in interprofessional learning. Methods: The pre-experimental design, pre and posttest design was used to examine a sample of 20 respondents which included the lecturers of nursing, midwifery and nutrition obtained by purposive sampling. Instrument to measure the readiness of lecturers using the RIPLS questionnaire. Result: The results of statistical tests using the T-Test found that the readiness of lecturers in the positive category where there was a change in readiness before and after being given an intervention in the form of interprofessional learning training with a Pvalue of 0.021. Conclusion: Educational institutions are recommended to start developing interprofessional education models that are mutually agreed upon and supported by clear facilities, policies and regulations. Subsequent research is expected to explore more appropriate interprofessional learning models through both qualitative and quantitative approaches